Development and validation of immunogenic cell death-related signature for predicting the prognosis and immune landscape of uveal melanoma - Hu, Yuanyuan; Cai, Jiayang; Ye, Meng; Mou, Qianxue; Zhao, Bowen; Sun, Qian; Lou, Xiaotong; Zhang, Hong; Zhao, Yin (Frontiers in Immunology, 2022)
Uveal melanoma (UM) is the most common primary intraocular malignant tumor in adults, and the main treatment for UM is currently surgery and radiation therapy. UM is highly susceptible to metastasis, with nearly half of all patients eventually metastasizing, and once metastasis occurs patients have a poor prognosis and are difficult to treat. Therefore, the identification of new and effective UM biomarkers is vital for the application of therapeutic strategies. Immunogenic cell death (ICD) is a type of regulatory cell death that activates adaptive immune responses and generates long-term immunological memory. There is evidence that ICD can promote anti-tumor immunity. Thus, ICD may be a potential immunotherapeutic strategy for UM. In the study, we analyzed the relationship between ICD-related genes expression and UM patient prognosis, somatic mutations, and tumor immune microenvironment. Importantly, we constructed a 5-genes ICD-related risk signature and identified it as a novel prognostic biomarker in UM patients. We found that the high-risk group had more immune cell infiltration and a worse prognosis than the low-risk group. In cellular experiments, we confirmed the high expression of FOXP3 in MUM2B and OCM-1A cell lines and that knockdown of FOXP3 markedly inhibited the proliferation of UM tumor cells.